Pemetaan dan Penyuluhan tentang Pengangguran Usia Produktif di Baubau - Samnia Samnia; Marlin Heepi Agung; Iin Handayani (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2022)
Productive-age unemployment is one of the main challenges in economic development in Baubau City. The lack of access to skills training, limited job market information, and low motivation for entrepreneurship are key factors contributing to the high unemployment rate among the productive-age population. This study aims to map the unemployment conditions in Baubau and implement a counseling and training program to enhance employment readiness and entrepreneurship skills. This study uses a qualitative descriptive approach through surveys, interviews, and Focus Group Discussions (FGD). The counseling program involves multiple stakeholders, including government agencies, businesses, and educational institutions. The results indicate that the program effectively increased participants' understanding of job search strategies, industry-based skills, and entrepreneurial interest. Evaluations show that employment readiness and entrepreneurship skills improved from 40% to 80% after training. With this program, the productive-age population in Baubau is expected to be better prepared for employment challenges and have alternative solutions for economic self-sufficiency. Strengthening collaboration among stakeholders is essential to ensure the sustainability and broader impact of similar programs.